PENGGUNAAN METODE IN THE NEWS UNTUK MENINGKATKAN KEMAMPUAN LITERASI INFORMASI SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan Kelas di Kelas XI MIIA 2 SMA Kartika XIX-1 Bandung) - Efik Mulyati; Tarunasena Ma'mur (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This research entitled ‘The use of in the news method to increase the students’ ability on information literacy in history learning (Classroom action research in twelfth grade-MIIA 2, SMA Kartika XIX-1 Bandung)’. After conducting the initial observation, the problem that occurs is the low ability of the students’ information literacy. It can be seen through the students’ habit that only concerns one resource in investigating a particular topic that relates to teaching material or in answering the questions given by the teacher. The students also do not exercise identification process on the goodness or the badness of the resource used to accomplish their assignments. Moreover, the students do not have the ability to process the information well. Most students directly copy the information obtained from the resource to finish their assignments. This study employs classroom action research with the use of Dave Ebbut’s research design. Through in the news methodology, the teacher emphasizes the students to investigate, process, and communicate many kinds of information from the resources used by them. Based on the analysis of this research, it shows that the use of in the news method can increase the students’ ability on information literacy in history learning in twelfth grade-MIIA 2, SMA Kartika XIX-1 Bandung. It can be seen from the enhancement of the students’ achievement in every implementation of cycle, the work on assignment, and group presentation.